Penerapan PSAK 45 Tentang Penyajian Laporan Keuangan Organisasi Nirlaba (Studi Kasus di Masjid Ar Rahman Kelurahan Sidomulyo Barat) - A, Adriani (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
Organizations that are not profit or profit oriented are usually called non-profit organizations. There are various types of non-profit organizations such as foundations according to their respective fields, including; social field, humanitarian field, and religious field. Mosques as a religious sector have an obligation to make financial reports as a form of accountability and report them to financial report users. This research aims to determine the accountability and transparency of mosque financial management and the conformity of financial reports with PSAK 45 at the Ar Rahman Mosque in West Sidomulyo District. The research method used is descriptive qualitative. With data collected using interviews with mosque administrators and other supporting documents. The results of this research indicate that the Ar Rahman Mosque has not implemented its financial reporting according to PSAK 45 standards. However, the recording process has been carried out in an open manner. The information obtained is that mosque administrators, especially the finance department, are very unfamiliar with the accounting term PSAK 45 itself because the educational background of mosque administrators is not from accounting, which is a problem with the proper implementation of accounting standards.